Examining whether affectively-charged motivations predict subsequent affective response during physical activity: An ecological momentary assessment study - Bridgette Do; Ryan E. Rhodes; Martina Kanning; Micaela Hewus; Genevieve F. Dunton; Genevieve F. Dunton (Frontiers Media S.A., 2022)
BackgroundEvidence suggests positive affective response during physical activity increases the likelihood of engaging in and maintaining regular activity exercise in the future. Elucidating antecedents for a positive affective response may help identify intervention strategies to increase activity. Affectively-charged motivations (e.g., desires, urges, dreading) have been posited as proximal antecedents to physical activity but have yet to be examined in terms of their influence on affective response in real-world settings. The current study used ecological momentary assessment (EMA) to examine within-subject effects of pre-physical activity affectively-charged motivation on subsequent affective response during physical activity.MethodsParticipants included 56 adults (M = 39.18 years, SD = 11.98; 67.86% female) who completed a 14-day smartphone-based EMA study. Prior to starting physical activity (time t), participants self-initiated an event-contingent EMA survey that assessed affectively-charged motivation for physical activity (i.e., rating scale from "dreading it" to "excited to do it"). EMA surveys prompted during subsequent physical activity (time t + 15 min) assessed affective response (i.e., feeling good-bad, energized-exhausted, thrilled-miserable, interested-bored, and relaxed-nervous). Multi-level linear regression models examined within-subject effects of pre- physical activity affectively-charged motivations on subsequent affective response during physical activity controlling for between-subjects effects of affectively-charged motivation, age, biological sex, time of day, and day of the week.ResultsOverall, there were N = 304 physical activity occasions in the analysis (M = 5.43, SD = 3.97). When individuals reported more positive affectively-charged motivation for physical activity than usual before physical activity occasions, they reported feeling more energized (Estimate = 0.22, p < 0.001), good (Estimate = 0.25, p < 0.001), thrilled (Estimate = 0.12, p = 0.02), and interested (Estimate = 0.24, p < 0.001) during subsequent physical activity. Affectively-charged motivation was not associated with feeling more relaxed (Estimate = 0.11, p = 0.13) during subsequent physical activity.ConclusionMomentary affectively-charged motivations predicted more positive affective response during subsequent physical activity among active adults. Future research can explore potential sources of intraindividual differences in affectively-charged motivations and further examine these associations with future physical activity behavior. To improve positive affective responses, interventions may boost affectively-charged motivations through real-time mobile prompting in naturalistic settings.